Building a Culture of Quality in Madrasas: The Strategic Role of School Committees - Sabar Indah Hikmawati; Muhammad Imam Khaudli; Siti Aimah; Fathiyah Mohd Fakhrudin (Institut Agama Islam An-Nawawi Purworejo, 2024)
The madrasa committee has an important role and function in building a culture of quality at MAN 2 Banyuwangi. The superior quality of MAN 2 Banyuwangi is the main target in madrasa management. This research aims to: (1) analyze the role and function of the madrasa committee in building a quality culture at MAN 2 Banyuwangi, (2) analyze the appropriate strategy for the madrasa committee to implement in building a quality culture at MAN 2 Banyuwangi, (3). identify the obstacles faced by the madrasa committee in building a culture of quality at MAN 2 Banyuwangi. This research includes field research using a qualitative approach. Data collection techniques in this research used observation, interviews and documentation. The data analysis uses Miles and Huberman's interactive analysis which consists of data reduction, data presentation and drawing conclusions. The results of this research: (1) the role and function of the committee in building quality is to be a controller, a mediator, and a manager of donations. (2) Strategy for building a quality culture at MAN 2 Banyuwangi, the committee team created 6 strategies, namely: utilizing committee figures, building networks, collaborating with community leaders, building public trust, branding image and regular meetings. (3) The obstacle for madrasah committees in building a quality culture is the different paradigms of each HR party which influence the performance of the committee, the awareness of committee members and the busyness of each member so that there is less focus on performance.